2014
DOI: 10.3892/mmr.2014.1885
|View full text |Cite|
|
Sign up to set email alerts
|

Generation of induced pluripotent stem cells using skin fibroblasts from patients with myocardial infarction under feeder-free conditions

Abstract: Abstract. Myocardial infarction (MI) is an increasing medical problem; however, its pathogenesis has yet to be elucidated and more effective treatment strategies are required. Induced pluripotent stem cells (iPSCs) were recently successfully generated using human somatic cells transfected with four transcription factors. The present study aimed to generate iPSCs from cells from patients with myocardial infarction. Six patients who had been diagnosed with myocardial infarction were enrolled in this study. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Published studies mainly focus on the association between MI and cardiomyocyte death, including apoptosis and necrosis [ 32 ]. Existing experiments in vitro revealed that miR-92a has effects on some cardiac diseases, such as endothelial inflammatory, atherosclerosis, and ischemia-reperfusion injury [ 25 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Published studies mainly focus on the association between MI and cardiomyocyte death, including apoptosis and necrosis [ 32 ]. Existing experiments in vitro revealed that miR-92a has effects on some cardiac diseases, such as endothelial inflammatory, atherosclerosis, and ischemia-reperfusion injury [ 25 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…7) If the ischemia or fibrosis reaction is continuously induced, the extracellular matrix will be excessively deposited, resulting in fibrous scar formation, which will further change the shape and structure of the heart and reduce the compliance of the heart. 8,9) Moreover, excessive accumulation of extracellular matrix easily induces arrhythmias and leads to permanent arrhythmia. 10) Therefore, preventing excessive myocardial fibrosis, late reactive fibrosis of MI, is an important research direction for interventional treatment of acute MI disease.…”
mentioning
confidence: 99%